Covid-19 pandemic? Mental health implications among nurses and Proposed interventions - Vasiliki Georgousopoulou; Panagiota Pervanidou; Pantelis Perdikaris; Efrosyni Vlachioti; Vaia Zagana; Ioanna Pavlopoulou; Vasiliki Matziou (AIMS Press, 2024)
Background: With its abrupt and huge health and socio-economic consequences, the coronavirus disease (COVID-19) pandemic has led to a uniquely demanding, intensely stressful, and even traumatic period. Healthcare workers (HCW), especially nurses, were exposed to mental health challenges during those challenging times. Objectives: Review the current literature on mental health problems among nurses caring for COVID-19 patients. Methods: This is a narrative review and critical evaluation of relevant publications. Results: Nurses experienced higher levels of stress, burnout, anxiety, depression, frustration, stigma, and depersonalization compared to other HCW. Factors that increased this symptomatology included concerns about infection or infection of family members, inadequate staff protective equipment, extended working hours, insufficient information, a reduced sense of security, and post-traumatic stress disorder. The factors that improved the psychopathology included a general positive attitude, job satisfaction, adequate information and education, harmonious group relationships, post-traumatic development, emotional intelligence, psychological counseling, mindfulness-based stress reduction, stable leadership, guidance, and moral and practical administrative support. Conclusions: Recent studies clearly show that nurses, especially women, are the most vulnerable subgroup among HCW and are particularly prone to mental health impacts during the COVID-19 pandemic. The documented mental health vulnerability of frontline nursing staff during the COVID-19 pandemic requires preventive nursing management actions to increase resilience and to develop relevant defense mechanisms.